Coastal Landform Constrains Dispersal in Mangroves - Triest, Ludwig; Van der Stocken, Tom (Frontiers in Marine Science, 2021)
Mangrove forests are dynamic ecosystems found along low-lying coastal plains along tropical, subtropical, and some warm-temperate coasts, predominantly on tidal flats fringing deltas, estuaries, bays, and oceanic atolls. These landforms present varied hydrodynamic and geomorphological settings for mangroves to persist and could influence the extent of within-site propagule transport and subsequent local regeneration. In this study, we examined how different landform characteristics may influence local genetic diversity, kinship, and neighborhood structure of mangrove populations. To do so, we considered independent populations of Avicennia marina, one of the most abundant and widespread mangrove species, located in estuarine and coastal bay environments spread across the Western Indian Ocean region. A transect approach was considered to estimate kinship-based fine-scale spatial genetic structure using 15 polymorphic microsatellite markers in 475 adult A. marina trees from 14 populations. Elevated kinship values and significant fine-scale structure up to 30, 60, or 90 m distances were detected in sheltered systems void of river discharge, suggesting a setting suitable for very local propagule retention and establishment within a neighborhood. Slopes of a linear regression over restricted distance within 150 m were significantly declining in each sheltered transect. Contrastingly, such a spatial structure has not been detected for A. marina transects bordering rivers in the estuarine systems considered, or alongside partially sheltered creeks, suggesting that recruitment here is governed by unrelated carried-away mixed-origin propagules. South African populations showed strong inbreeding levels. In general, we have shown that A. marina populations can locally experience different modes of propagule movement, explained from their position in different coastal landforms. Thus, the resilience of mangroves through natural regeneration is achieved by different responses in coastal landforms characterized by different hydrodynamic conditions, which can be important information for their management and protection within the variety of coastal environments.